2022
DOI: 10.1088/1755-1315/1115/1/012085
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Quality of Betung Bamboo (Dendrocalamus asper) from Forest Area with Special Purpose (FASP) Pondok Buluh, Simalungun, North Sumatera

Abstract: The FASP Pondok Buluh is located in Dolok Panribuan District, Simalungan Regency, Sumatera Utara, which has uniqueness due to the number of bamboo species found in this area, such as Betung Bamboo. This bamboo has a long fiber and is suitable for pulp and paper materials. This research aims to measure the dimension of Betung Bamboo and its fiber derivatives value for the eligibility of pulp and paper material. A total of 3 stems of Betung Bamboo were cut, and samples were taken in the form of a disc with a len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…In SPB A. longipes, the coefficient of rigidity and flexibility ratio were 0.37 and 0.54, respectively. This value was comparable to the coefficient of rigidity (0.25-0.31) and flexibility ratio (0.38-0.54) of bamboo fiber [25]. The results of the fiber morphology analysis showed that samples from SPB of A. longipes were suitable material for paper packaging.…”
Section: Fiber Morphology and Fiber Derivatessupporting
confidence: 69%
“…In SPB A. longipes, the coefficient of rigidity and flexibility ratio were 0.37 and 0.54, respectively. This value was comparable to the coefficient of rigidity (0.25-0.31) and flexibility ratio (0.38-0.54) of bamboo fiber [25]. The results of the fiber morphology analysis showed that samples from SPB of A. longipes were suitable material for paper packaging.…”
Section: Fiber Morphology and Fiber Derivatessupporting
confidence: 69%